Atomoxetine in Early Pregnancy and the Prevalence of Major Congenital Malformations:A Multinational Study - Bröms, Gabriella; Hernandez-Diaz, Sonia; Huybrechts, Krista F; Bateman, Brian T; Kristiansen, Eskild Bendix; Einarsdóttir, Kristjana; Engeland, Anders; Furu, Kari; Gissler, Mika; Karlsson, Pär; Klungsøyr, Kari; Lahesmaa-Korpinen, Anna-Maria; et al. (The Journal of Clinical Psychiatry, 2023)
Objective: Most research on safety of attention-deficit/hyperactivity disorder (ADHD) medications during pregnancy concerns central nervous system stimulants, while little is known about the safety of atomoxetine, a primary treatment alternative. We assessed the prevalence of major congenital malformations overall, and cardiac malformations and limb malformations specifically, after first-trimester exposure. Methods: In this cohort study, we included all approximately 2.4 million pregnancies ending in live births recorded in the population-based nationwide health registers of Denmark, Iceland, Norway, and Sweden (2003-2017) and approximately 1.8 million publicly insured pregnancies ending in live births recorded in the US Medicaid Analytic eXtract (MAX, 2001-2013) health care claims database. We compared the prevalence of major congenital malformations in the newborn among pregnancies exposed and unexposed to atomoxetine. For each country, we calculated prevalence ratios (PRs), crude and stratified by propensity scores (PSs). We pooled the country-specific PS strata to obtain a PR adjusted for potential confounding factors. Results: We identified 368 pregnancies exposed to atomoxetine during the first trimester in the 4 Nordic countries and 622 in the US. The pooled crude PR for any major congenital malformation was 1.18 (95% CI, 0.88-1.60), and the adjusted PR was 0.99 (95% CI, 0.74-1.34). For cardiac malformations, the adjusted PR was 1.34 (95% CI, 0.86-2.09). For limb malformations, the adjusted PR was 0.90 (95% CI, 0.38-2.16). Conclusions: After atomoxetine exposure in early pregnancy, we observed no increase in major congenital malformations overall and, although with some uncertainty due to sample size, no statistically increased risk estimates for cardiac malformations and limb malformations.